Effect of a mindfulness intervention on patients admitted after multisystem trauma. (July 2020) - Clement, Elizabeth; Yoon, Jenny; Sutherland, Tala; Tsang, Bonnie; Fawcett, Vanessa; Kim, Michael; Widder, Sandy
Background: The incidence of depression, anxiety, and post-traumatic stress disorders is reported to be as high as 50% in trauma patients. The perpetual negative emotions and state of mind in these disorders predisposes patients to negative mental health outcomes. Mindfulness, on the other hand, helps people to process their experience and emotions in a non-judgmental manner, and recently, there has been increased utilization of mindfulness-based therapies for the treatment of mental health conditions. This proof-of-concept study evaluates the use of a mindfulness-based online application in patients admitted to the trauma service at a Level 1 Trauma Centre. Methods: Trauma patients who were English speaking, over the age of 18, and without brain injury or pre-existing neurocognitive disorder were included. Participants completed the Depression Anxiety Stress Scale (DASS)-21 to assess level of depression, anxiety, and stress, and the Connor-Davidson Resilience Scale (CD-RISC) to assess level of resiliency. Then, after 28 consecutive days of practicing mindfulness using the app 'Stop, Breathe, and Think, ' the questionnaires were repeated and an exit survey conducted. Results: For this study, 13 participants were enrolled, 2 withdrew, and 5 were lost to follow-up. The mean DASS-21 score at time enrollment was 16.4 and was 11.2 at follow-up ( p = 0.10). There were no differences between the level of depression and stress from enrollment to follow-up, but there was significant decrease in anxiety symptoms from 7.2 to 3.0 (<0.05). CD-RISC scores at enrollment and follow-up were 77.8 and 81 ( p = 0.23), respectively. At the time of exit interview, 67% of patients continued to use the application three to four times a week and 67% responded they plan to continue using the application. In addition, 83% of patients always or often felt better after practicing mindfulness and stated they would recommend the application to others. Conclusions: Mindfulness shows promising potential to decrease psychological distress in trauma patients.